KINERJA PEMERINTAH DAERAH KABUPATEN/KOTA DI PULAU SUMATERA - Abdullah, Abdullah; Mardatillah, Sri (UNIB Press, 2017)
This study aims to analyze improve of the financial performance local government in Sumatera island period 2012-2016 measured through the calculating the degrees decentralization ratio,dependency ratio, local finance activity ratio, effectiveness ratio, efficiency ratio, the ratio of harmony and growth ratio. This research used the descriptive approach.The sample in this research was local government Sumatera island period 2012-2016. Method of data collection had purposive sampling technique. The analysis data using descriptive analysis and trend analysis to saw increase of financial performance.The result of this study indicate that performance of the financial local government in Sumatera island having an increase seen from degrees decentralization ratio,dependent ratio, local finance activity ratio,the ratio of harmony, and growth expenditure ratio. While the effectiveness ratio, efficiency ratio, and growth income ratio show fluctuations in the performance of the financial local government in Sumatera island.